2015
DOI: 10.1017/s0022029915000539
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative variations on Calabrian Provola cheeses stored under different packaging conditions

Abstract: Calabrian Provola cheese, an Italian typical dairy product, is commonly sold unwrapped with an expiry date of 45 d. The influence of different packagings and subsequent storage at 4 and 7 °C on maintaining cheese quality and prolonging its shelf life was evaluated. The following packaging systems were used: Polyamide/Polyethylene pouch under vacuum; Polyethylene/Polyethylene terephthalate lid over a Polyethylene/Ethylene vinyl alcohol/Polyvinyl Chloride + Polyvinyl alcohol thermoformed tray; Polyethylene/Ethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
1
13
0
1
Order By: Relevance
“…A ausência de embalagem em mais de Nota: *A = valores absolutos e R = valores relativos 90% dos locais de venda dos queijos cabacinha (Tabela 2) é também outro fator preocupante e que precisa ser resolvido, pois se gundo Piscopo et al (2015) a ausência de in vólucro pode facilitar o desenvolvi mento mi crobiológico indesejado. Porém, esta prá ti ca precisa ser mais pesquisada, pois pode alterar as características do produto tradicional.…”
Section: Resultsunclassified
“…A ausência de embalagem em mais de Nota: *A = valores absolutos e R = valores relativos 90% dos locais de venda dos queijos cabacinha (Tabela 2) é também outro fator preocupante e que precisa ser resolvido, pois se gundo Piscopo et al (2015) a ausência de in vólucro pode facilitar o desenvolvi mento mi crobiológico indesejado. Porém, esta prá ti ca precisa ser mais pesquisada, pois pode alterar as características do produto tradicional.…”
Section: Resultsunclassified
“…Authors decided to evaluate the qualitative changes first after 10 days from packaging because the expiry date of unpackaged Provola cheeses was of 45 days, as reported in a linked previous work concerning the packaging with conventional materials (Piscopo et al, 2015). We compared the changes with 0 days, immediately after manufacturing.…”
Section: Generallymentioning
confidence: 99%
“…For textural analysis of CPc authors followed the method, equipment and instrumental parameters reported in a previous published work on Provola cheeses (Piscopo, Zappia, De Bruno, & Poiana, 2015). The Total Nitrogen (TN) of samples was quantified as described by Lynch & Barbano (2002).…”
Section: Physical Microbiological and Chemical Analyses Of Calabriamentioning
confidence: 99%
See 2 more Smart Citations